Sonata for cello and piano, op 43, 3rd movement - Esposito, Michele; Butt, William; Coburn, Lance (Champs Hill Records, 2013)
Michele Esposito spent almost his whole professional life in Ireland, and he was a respected and hugely influential figure throughout that time - indeed, a very lynch-pin of Irish musical life. Though his own compositions have suffered a period of eclipse, they are undergoing a gradual revival, as the present recording demonstrates.
Esposito: Violin and cello sonatas
William Butt (Cello); Lance Coburn (Piano)
Keywords: Music; Esposito, Michele, 1855-1929; Cello and piano music; Sonatas (Cello and piano)